Mitochondrial DNA (mtDNA) variants in the European haplogroups HV, JT, and U do not have a major role in schizophrenia. Issue 7 (17th August 2014) - Torrell, Helena; Salas, Antonio; Abasolo, Nerea; Morén, Constanza; Garrabou, Glòria; Valero, Joaquín; Alonso, Yolanda; Vilella, Elisabet; Costas, Javier; Martorell, Lourdes
<x xml:space="preserve">Abstract</x> It has been reported that certain genetic factors involved in schizophrenia could be located in the mitochondrial DNA (mtDNA). Therefore, we hypothesized that mtDNA mutations and/or variants would be present in schizophrenia patients and may be related to schizophrenia characteristics and mitochondrial function. This study was performed in three steps: (1) identification of pathogenic mutations and variants in 14 schizophrenia patients with an apparent maternal inheritance of the disease by sequencing the entire mtDNA; (2) case‐control association study of 23 variants identified in step 1 (16 missense, 3 rRNA, and 4 tRNA variants) in 495 patients and 615 controls, and (3) analyses of the associated variants according to the clinical, psychopathological, and neuropsychological characteristics and according to the oxidative and enzymatic activities of the mitochondrial respiratory chain. We did not identify pathogenic mtDNA mutations in the 14 sequenced patients. Two known variants were nominally associated with schizophrenia and were further studied. The MT‐RNR2 1811A > G variant likely does not play a major role in schizophrenia, as it was not associated with clinical, psychopathological, or neuropsychological variables, and the MT‐ATP6 9110T > C p.Ile195Thr variant did not result in differences in the oxidative and enzymatic functions of the mitochondrial respiratory chain. The patients with apparent maternal inheritance of schizophrenia did not exhibit any mutations in their mtDNA. The variants nominally associated with schizophrenia in the present study were not related either to phenotypic characteristics or to mitochondrial function. We did not find evidence pointing to a role for mtDNA sequence variation in schizophrenia. © 2014 Wiley Periodicals, Inc.